Undermining the experience of task‐related success by illegitimate tasks: A three‐wave study. - Semmer, Norbert K.; Kern, Marcel; Mühlethaler, Céline M.; Kälin, Wolfgang; Tschan, Franziska; Jacobshagen, Nicola; Meier, Laurenz L.; Elfering, Achim (Applied Psychology: An International Review, 2025)
Dealing well with tasks that characterize one's occupational role should confirm occupational identity and induce pleasurable feelings in terms of task‐related success. However, some tasks are illegitimate, with employees thinking they should not have to do them because they are unreasonable (not part of their occupational role) or unnecessary (should not exist at all). Illegitimate tasks (ILTA) constitute an offense to occupational identity, and completing them should induce feelings of success to a lower degree than completing legitimate tasks. They might even induce feelings of failure, notably if impairing core performance. In a three‐wave study in two Swiss companies (N = 160), structural equation modeling with lagged paths constricted to equality yielded significant paths from ILTA to success experiences for the lagged and the synchronous paths; for failure, only the synchronous effect was significant. Thus, the hypothesis that ILTA dampens success experience is largely supported, whereas effects on failure experiences may be restricted to short time periods. Results are largely in line with the assumption that ILTA does not contribute to affirming one's occupational identity, thus extending the nomological net of illegitimate tasks and suggesting a stronger focus on role‐related content of task design and on task‐related success.